Two cases of X-linked retinoschisis with different spectral domain optical coherence tomography findings - Leng, Theodore (Dove Medical Press, 2012)
Spectral domain optical coherence tomography was used to image the maculae of two brothers who had the diagnosis of X-linked retinoschisis maculopathy. One patient demonstrated a large foveal cyst in one eye and a lamellar macular hole in the fellow eye. The second patient demonstrated small retinal cysts in multiple layers of the retina. Spectral domain optical coherence tomography allowed high-resolution imaging and characterization of the features in X-linked retinoschisis in these patients, and it highlighted the variability of the same genetic disease, even in one family.